Promosi Pada Toko Baju SANF Collection - Silvia Agustina; Puji Isyanto (Journal Of Informatics And Busisnes, 2024)
Product promotion is an important element in today's business strategy to drive sales and create brand awareness. Apart from increasing sales, promotions aim to inform, persuade and remind consumers about certain products or brands. The information presented in promotions must be interesting and clear, including the uses, advantages and disadvantages of the product to influence consumer purchasing decisions. Effective promotion also helps in positioning the product to be top of mind among consumers. Companies must determine the right promotional tools, both through offline media such as promotional events and print media, and online such as social media and email marketing, to achieve optimal results. The success of promotions depends on understanding the market, creativity in implementation, and adaptation to technological developments and consumer trends. SANF Collection Clothing Store, for example, utilizes a combination of offline and online promotions to reach more consumers, increase brand awareness, and strengthen customer loyalty, which ultimately supports business growth and sustainability.